Clinical Features and T‐Cell Repertoire of Chronic Myeloid Leukemia Patients Who Attempt Discontinuation of Tyrosine Kinase Inhibitors: The ISAC‐TFR Study - Hiroshi Ureshino; Yukio Nakamura; Yemima Budirahardja; Iwao Nozawa; Keisuke Kidoguchi; Kazuharu Kamachi; Shinya Kimura (Cancer Medicine)
ABSTRACT Background While tyrosine kinase inhibitor (TKI) discontinuation is an established therapeutic goal, up to 60% of patients relapse after the first attempt. The feasibility of a second or third attempt at TKI discontinuation remains uncertain. Immune surveillance, particularly T‐cell and natural killer (NK) cell responses, may influence treatment‐free remission (TFR), although no definitive biomarkers for predicting sustained TFR have been identified. Methods This retrospective study included 57 chronic myeloid leukemia (CML) patients who attempted TKI discontinuation. Clinical outcomes after the first, second, and third TFR attempts were analyzed, and T cell receptor (TCR) and B‐cell receptor (BCR) repertoire analyses were conducted on peripheral blood samples from 14 patients to investigate the immune landscape associated with TFR. Results TFR1 at 1 year was 67.9% (95% confidence interval [CI], 53.9%–78.4%). Sixteen patients attempted a second discontinuation, achieving a 1‐year TFR2 rate of 31.2% (95% CI, 11.4%–53.6%). Patients maintaining BCR::ABL1 mRNA levels below MR4.5 at 3 months post‐TKI discontinuation had a significantly lower risk of relapse (HR, 0.099; 95% CI, 0.012–0.829; p = 0.033). TCR repertoire analysis did not reveal distinct clonal expansions of T cells; however, a significant age‐related decline in T‐cell diversity was observed. Conclusion T‐cell immunity in CML patients who have achieved a deep molecular response (DMR) may closely approximate that observed in healthy individuals.